Effect of Disruptive Technology on Small and Medium Industries in Kano Nigeria - Umma A. U. Mani; Umar Haruna; Buba Musa Pulka (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
The impact of disruptive technology on small and medium industries in Kano is a topic of increasing relevance in today's dynamic business landscape. This study delves into the effects of disruptive technology adoption on SMEs in Kano, emphasizing its implications for business growth, competitiveness, and economic development. Drawing on research by Moravec and Martínez-Bravo (2023) and Geda (2022), the paper elucidates how integrating disruptive technologies can lead to enhanced operational efficiency, innovation, and sustainability for businesses in Kano. The findings underscore the importance of understanding the implications of disruptive technology on SMEs to drive strategic decision-making, policy formulation, and technological readiness. Recommendations for stakeholders include developing technology adoption frameworks, promoting skills development, enhancing digital infrastructure, supporting research and development, and ensuring data privacy and security measures. By aligning these recommendations with the needs of small and medium industries in Kano, stakeholders can capitalize on the opportunities presented by disruptive technology, foster a culture of innovation, and contribute to the overall economic development and competitiveness of SMEs in the region.